Міжнародні стандарти незалежності та безсторонності суду в кримінальному процесі України - Коровайко, О. І.; Korovaiko, O. I. (Право і безпека. – 2016. – № 4 (63). – С. 65-70, 2016)
На підставі аналізу юридичної літератури та чинного кримінального процесуального законодавства та з урахуванням практики Європейського суду з прав людини розглянуто проблеми реалізації міжнародних стандартів незалежності та безсторонності суду в кримінальному судочинстві України. Визначено, що вітчизняне кримінальне процесуальне законодавство повинно вдосконалюватись у напрямі формування механізму належного забезпечення дотримання вимог незалежності та безсторонності суду під час розгляду кримінального обвинувачення. Запропоновано уточнені формулювання завдань кримінального судочинства, перелік обставин, що виключать участь суддів у кримінальному судочинстві, наведено пропозиції щодо вдосконалення процедури відводів.

Based on the analysis of legal literature, the current criminal procedural law and considering the existing practice of the European Court of Human Rights (ECHR) the author has studied the problems of implementing international standards of independence and impartiality of the judiciary in criminal proceedings of Ukraine. It has been determined that the domestic criminal procedural law should be improved towards the formation of the mechanism of proper guaranteeing the requirements of independence and impartiality of the judiciary in criminal prosecution. It has been stated that the current criminal procedural legislation of Ukraine, compared with the previous one, much more attention is paid to establishing guarantees of compliance with the independence and impartiality of the judiciary as elements of the right to a fair trial. The author has stressed on the necessity of clarifying formulation of the tasks of criminal proceedings aimed at extending the requirements of impartiality in all judicial stages of the process. The author has offered to add the list of circumstances set by the Criminal Procedural Code of Ukraine that preclude the participation of the investigative judge, a judge or a juror in criminal proceedings, by such circumstances prevalent in the national process and the practice of the ECHR as giving by the judge public assessment of the nature of the case and its kinship with the other judges, who participated in the proceedings. The feasibility to improve the procedure of a judge and jury’s disqualification during the peer review of the case has been revealed.

На основании анализа юридической литературы и действующего уголовного процессуального законодательства с учётом существующей практики Европейского суда по правам человека рассмотрены проблемы реализации международных стандартов независимости и беспристрастности суда в уголовном судопроизводстве Украины. Определено, что отечественное уголовное процессуальное законодательство должно совершенствоваться в направлении формирования механизма надлежащего обеспечения соблюдения требований независимости и беспристрастности суда при рассмотрении уголовного обвинения. Предложены уточнённые формулировки задач уголовного судопроизводства, перечень обстоятельств, исключающих участие судей в уголовном производстве, даны предложения по совершенствованию процедуры отводов.
Международные стандарты независимости и беспристрастности суда в уголовном судопроизводстве Украины
Коровайко, О. І. Міжнародні стандарти незалежності та безсторонності суду в кримінальному процесі України / О. І. Коровайко // Право і безпека. – 2016. – № 4 (63). – С. 65-70.
Коровайко О. І. "Міжнародні стандарти незалежності та безсторонності суду в кримінальному процесі України." Право і Безпека 4 (2016): 65-70.
Korovaiko, O.I. (2016), “International standards of independence and impartiality of the judiciary in criminal proceedings of Ukraine” [“Mizhnarodni standarty nezalezhnosti ta bezstoronnosti sudu v kryminalnomu protsesi Ukrainy”], Pravo i Bezpeka, No. 4, pp. 65–70.
Keywords: Кримінально-процесуальне право. Criminal and Procedure Law. Уголовное процессуальное право; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; судопроизводство; международные стандарты судопроизводства; независимость суда; беспристрастность суда; право на справедливый суд; criminal proceedings; litigation; international standards of justice; independence of the judiciary; impartiality of the court; right to a fair trial; судове провадження; міжнародні стандарти судочинства; кримінальне провадження; незалежність суду; безсторонність суду; право на справедливий судовий розгляд